Flipbook-Based E-Module Development on the Theme of Changes in Indonesian Society During the Colonial Period and the Growth of Nationalism for Junior High School - Zharifah Ramadhani, Nur; Maharani, Bunga; Rahma Zahira, Qonita (Institut Agama Islam Negeri Madura, 2026)
The purpose of this study was to develop flipbook-based teaching materials for social studies lessons for eighth-grade students at MTs Negeri 2 Malang. This research is important to do because it can answer problems related to the limited number of printed learning resources in schools, UKBM sources and the like that explain more towards theory than practice so that they create a boring classroom climate, and the limitations of creative learning media used by teachers. Research using Researh and Development method or development research using ADDIE stages, namely analyze (analysis), design (designing), development (creating), implementation (applying), and evaluation (evaluating). The feasibility validation test was collected using a 1-5 scale questionnaire with details from not feasible, less feasible, quite feasible, feasible, and very feasible. The validation test was conducted by two experts who understand learning materials. The results of the feasibility validation test of teaching materials consist of the feasibility of content, language, and presentation conducted by validator 1 and validator 2 explaining that the interpretation of the feasibility of flipbook teaching materials can be declared very feasible. The results of responses from students which include learning components, quality, function, and appearance are declared very good. So that flipbook-based teaching materials developed to overcome the lack of teaching materials in social studies subjects can make students better at accessing material.